Profile of Critical Thinking Skills of Phase F Learning in Chemistry Subjects Acid-Base Material - Dini Catur Anisah; Harun Nasrudin; Sukarmin (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to describe the profile of critical thinking skills of Phase F students at Al-Azhar Menganti High School in the chemistry subject of acid-base material. This research is a quantitative and qualitative descriptive research. Data collection techniques are questionnaires, tests, and interviews. The research was conducted at Al-Azhar Menganti High School with chemistry teachers and 37 students in class XII. The results showed that the profile of students' critical thinking skills was low in the category of less and very less with only 36.93% of students who were able to interpret; 17.12% analysis; 21.17% inference; 33.33% evaluation; and 36.04% explanation with the factors that caused the low critical thinking skills of students were inappropriate learning models and lack of learning tools that could facilitate in improving critical thinking skills.